Board effects on innovation in family and non-family business - Gonzáles-Bustos, Juan Pablo; Hernández-Lara, Ana Beatriz; Li, Xiaoni (Heliyon, 2021)
This paper contributes to the corporate governance and innovation literature by providing empirical evidence with respect to the influence of composition of the board and its leadership structure on innovation. Also, this study seeks to investigate if such influence differs when comparing family and non-family business. Data were collected from 86 Spanish companies of innovative sectors from 2003 to 2014. The results show that innovation is affected positively by board size, especially in the case of family businesses, and gender diversity, especially in non-family businesses. Similarly, findings also point out that duality is better than the independence of functions in the case of non-family businesses. Finally, obtained results support that independent directors have a negative impact on innovation and such negative influence is even stronger in family firms. These findings contribute to an inconclusive literature regarding board effects on innovation, highlighting different recommendations depending on whether the companies are family businesses or not.
Keywords: board of directors; innovation; family businesses; gender; duality; independent directors; corporate governance; organizational theory; management; business management; strategic management; research and development; Emerging; Scopus